Evaluation of Thermodynamic Functions for Complexation Reactions in 1:1:1 Ternary Lanthanide(III) EGTA-SA/SSA/DNSA Systems - Kaurav, M.S. (Asian Journal of Chemistry, 2010)
Formation of 1 : 1 : 1 ternary complex species (MAL) has been inferred and the relevant equilibrium has been established from pH measurements on the interaction of M3+ ions {M= Tb(III), Dy(III), Ho(III) and Er(III)} with ligand A [A = ethylene glycol bis(2-aminoethyl ether)-N,N,N´,N´-tetraacetic acid (EGTA)] in the presence of the ligand L (L = SA/SSA/DNSA) in aqueous medium at varying ionic strengths of 0.05, 0.10 and 0.15 and at varying temperatures 25, 35 and 45ºC. A treatment has been worked out for obtaining information on the extent of metal ion distribution among the various species over the entire pH-range of study. Thermodynamic stability constants together with thermodynamic parameters and relative stabilization has been evaluated and correlated on the basis of basicity, denticity and statistical aspects.